Time motion study in work process using promodel approach - Bon, Abdul Talib; Ariffin, Aliza (2010)
The purpose of this research is to improve production capabilities for Small Medium Enterprise (SME) industry. Research focused on SME, which produce chili sauce. This research used Time and Motion technique to improve work process at SME, and the research objectives towards accomplished this study is to identify problems in the production work process and improved it in terms of production time, number of process and production layout by proposing an efficient work process to SME. This research used systematic observation; process chart and stopwatch time study as research methodology. Stat Fit and Pro Model Software are used for data testing and develop new work process. The improvement of work process was executed by eliminating and combining of work process, which reduces production time, number of process and space utilization.